Systemic lupus erythematosus and implications for the oral cavity - Cardoso, Inês Lopes (2020)
Systemic Lupus Erythematosus affects several people around the world and because it is characterized as a chronic inflammatory disease of multifactorial origin, and with systemic impairment, great attention must be paid from diagnosis to treatment in order to optimize the entire follow-up of the patient. The dental doctor plays an important role in the diagnosis of the condition and must be attentive to the early signs that can appear in the oral cavity with a frequency of up to 21%. In this way, through this bibliographic review, which has as main goal to correlate Systemic Lupus Erythematosus with its direct consequences in the oral cavity, it will be possible to help dentists in the diagnosis, to understand in detail the development of the disease and what attitude should be taken in its presence.